Investor activism, managerial responsiveness, and corporate social performance - David, Parthiban; Bloom, Matt; Hillman, Amy J. (Strategic Management Journal, 2007)
Abstract We study relationships between shareholder proposal activism, managerial response, and corporate social performance (CSP). We find that shareholder proposal activism reduces CSP. We infer that rather than pressuring firms to improve CSP, activism may engender diversion of resources away from CSP into political activities used by managers to resist external pressures and retain discretion. We also find that managers are more likely to settle proposals filed by ‘salient’ shareholders (i.e., those with power, legitimacy, and urgency). Settlement with salient shareholders, however, also reduces CSP, suggesting that managers' responses are symbolic; i.e., they settle with salient shareholders to demonstrate conformance but continue to resist making the substantive changes to core policies that may compromise their discretion. Copyright © 2007 John Wiley & Sons, Ltd.